The Influence of NPL and LDR on Profitability with Car as a Mediation Variable at PT BPR Dana Mandiri Bogor - Nana Arisma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the effect of Non Performing Loans (NPL) and Loan to Deposit Ratio (LDR) on Profitability (ROA) at PT. BPR Dana Mandiri Bogor from 2017 to 2021, with the capital adequacy ratio (CAR) as a mediating variable. This research effort contained a total of thirty samples. Non-participant observation is the method used in this study to obtain data. The data analysis technique used in this particular study project is tabular analysis. The results and interpretation of the analysis of this study indicate that both NPL and LDR have a significant effect on ROA, while CAR does not have a significant positive or negative effect on ROA. The relationship between NPL and ROA is only moderated by CAR.